Broad-specific monoclonal antibody based IACs purification coupled UPLC-MS/MS method for T-2 and HT-2 toxin determination in maize and cherry samples. Issue 1 (1st January 2020) - Li, Yanshen; Lin, Shaoxia; Wang, Yunhui; Mao, Xin; Wu, Yongning; Liu, Yunguo; Chen, Daquan
ABSTRACT: In this work, broad-specific monoclonal antibody based immunoaffinity columns (IACs) coupled to ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) for purification and determination of T-2 and HT-2 toxin in maize and cherry samples. Based on broad-specific anti-T-2 monoclonal antibody, the prepared IACs could be used for both T-2 and HT-2 purification with cross reactivity values at 100% for T-2 and 108% for HT-2. Column capacity was 3.14 μg mL −1 gel for T-2 toxin, and 3.20 μg mL −1 gel for HT-2 toxin. After 10 cycles of usage at intervals of 2 days, column capacity decreased to 0.85 μg mL −1 gel for T-2 and 1.22 μg mL −1 gel for HT-2 toxin. The developed method exhibited high sensitive results with limit of detection (LOD) lower than 0.35 μg kg −1 and 1.42 μg kg −1 .